Children internet usage: opportunities for self development - Omar, Siti Zobidah; Daud, Azlina; Hassan, Md. Salleh; Bolong, Jusang; Teimmouri, Misha (Elsevier (ScienceDirect), 2014)
Children are spending more and more time on the Internet. Are there any opportunities from such exposure to the Internet? This study looks at six types of children positive use of the Internet to measure opportunities gain by children. These are: information, communication, entertainment, participation, creativity and expression. The descriptive analysis of data on children ages 9 to 16 years showed that most children in Malaysia are enjoining opportunities on the Internet through information searching, communication and entertainment activities. Children's online opportunity is inter-related with their availability and capability of the Internet technology. If children enjoy i.e. if there are available Internet technologies with high speed user interface connectivity, children will be more disposed to use the Internet for self development.